FACTORS AFFECTING CONSUMER'S LOCAL FRIED CHICKEN PURCHASE DECISIONS - Andrean Emaputra; Muhammad Kusumawan Herliansyah (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
There were eight local fried chickens in Special Disrict of Yogyakarta. It makes a question about what factors cause successful and unsuccessful local fried chicken. Then, a consumer survey that sought the level of customer satisfaction was done using a questionnaire. The survey involved 242 respondents that had eaten the local fried chicken. The result shows that the easiness of the outlet to be reached by the consumer and the products price that is competitive are the main factors to lead the local fried chicken to be successful in the market place.